(untitled) (Fiep Bulletin - online, 2013)
The present study it had as objective to verify the effect of 10 months of a program of labor gymnastics, executed for Professors and trainees of Physical Education, and Physiotherapists, destined to the employees of the Brazilian Institute of Tourism - Embratur - Brasilia. The sample was composed initially for 153 servers of the Embratur, but 139 had only concluded all the inquiry protocol. In general way, the elaborated exercises had involved: the cervical region, the superior members, the inferior trunk and members. The investigated sample considered excellent the proposal of the project provided in 80% of the total of the involved servers in the study. When one is about health in the work, the Embratur has looked inside of its attributions and limitations, to offer the servers, a healthful and acolhedor environment, where the same it can search answers that make it to feel better working with excess of responsibilities exactly. To prevent the riots osteomusculares in the work environment is function of project of QVT (labor gymnastics) in the organizations, mainly of profile the humanist.